Development of An Ethnoscience Module on the Environmental Pollution Theme to Improve Community Early Literacy - Arianingrum, Dena; Wahyuni, Sri; Rusdianto, Rusdianto (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2024)
Early literacy skills are crucial foundational abilities necessary for a more meaningful life. The low levels of early literacy within society must be addressed to foster good literacy habits. Developing an ethnoscience module themed around environmental pollution can help improve community early literacy skills. This study aims to (1) assess the validity of the ethnoscience module on environmental pollution, (2) evaluate the practicality of the ethnoscience module on environmental pollution, and (3) determine the effectiveness of the ethnoscience module on environmental pollution. The research employs the ADDIE methodology: (analysis) problem analysis, (design) module design, (development) module development, (implementation) module implementation, and (evaluation) module evaluation. The study’s findings indicate that (1) the ethnoscience module on environmental pollution is highly valid with a score of 87.81%, (2) the module is very practical with a score of 90,97%, and (3) the module is highly effective, achieving an N-Gain score of 0.8 and a community response rate of 86.25% in the very good category. The research and development results conclude that the ethnoscience module on environmental pollution can significantly enhance early literacy skills in the community.